The impact of internet use on old-age support patterns of middle-aged and older adults - Wang, Jingyi; Gao, Lifei; Wang, Guojun; Hu, Baibao (Frontiers in Public Health, 2023)
Background The trend towards low fertility and low mortality is prominant worldwide. The accelerating ageing and the pressure on public pensions are making the “dependent pattern of old-age support”, which relies on family and government, unsustainable. It is urgent for people to change their mindset about ageing and to develop a sense of “relying on themselves for oldage support”. Methods This study incorporates the commercial pension insurance, formal care and the attitude towards independent old-age support pattern into the framework of “independent pattern of old-age support”, using the probit regression model and instrumental variables approach to examine the impact of internet use on old-age support patterns of middleaged and older people based on the CGSS 2012–2018 five-period data. Results The more frequent internet use increased the likelihood of purchasing commercial pension insurance, accepting formal care, and endorsing independence in later life. The internet can promote the acceptance of independent pattern of old-age support by delivering information and facilitating social interaction. Discussion Consistent with previous research, this study finds that internet use can promote the purchase of commercial pension insurance. There are no relevant studies on the impact of internet use on formal care and attitude towards independent old-age support pattern. Our finding provides important empirical and theoretical references for ageing countries to further transform old-age support patterns.